Analisis Perbandingan Kelengkapan Rekam Medis Berdasarkan Metode Analisis Kuantitatif dengan Analisis Closed Medical Record Review di Rumah Sakit Kanker “Dharmais” - Mohammad Yusuf Setiawan; Lily Widjaja (Indonesian of Health Information Management Journal (INOHIM), 2020)
AbstractMedical record is a file that contains records and documents about patient identity, examination, treatment, actions and other services that have been provided to patients. Medical records must be made immediately and completed after the patient receives the service. Examination of the completeness and quality of medical records using quantitative medical record analysis methods and Closed Medical Record Review. This study is intended to compare the completeness of the Medical Record Based on Quantitative Analysis Method with the Analysis of Closed Medical Record Review in "Dharmais" Cancer Hospital. The type of this research is analytic descriptive research with cross sectional approach. The sample size in this study was 200 cases of medical records using simple random sampling technique. Data analysis using chi square test. The results of quantitative analysis of medical records showed the completeness of medical records was 82.84%, and incomplete was 17.16%. In the closed medical record review analysis shows the completeness of the medical record of 93.53%, and incomplete of 6.47%. Chi square test results showed that there was no significant difference in the proportion of completeness between the results of the Closed Medical Record Review Analysis and the results of the Quantitative Analysis of medical records (p value = 0.437> 0.05).Keyword:  Medical Record, Quantitative Analysis of Medical Records, Closed Medical Record Review Analysis, Cancer Hospital "Dharmais". AbstrakRekam medis merupakan berkas yang berisikan catatan dan dokumen tentang identitas pasien, pemeriksaan, pengobatan, tindakan dan pelayanan lain yang telah diberikan kepada pasien. Rekam medis harus dibuat segera dan dilengkapi setelah pasien menerima pelayanan. Pemeriksaan kelengkapan dan kualitas rekam medis menggunakan metode analisis kuantitatif rekam medis dan Closed Medical Record Review. Penelitian ini dimaksudkan untuk membandingkan Kelengkapan Rekam Medis Berdasarkan Metode Analisis Kuantitatif dengan Analisis Closed Medical Record Review di Rumah Sakit Kanker “Dharmais”. Jenis penelitian ini yaitu penelitian deskriptif analitik dengan pendekatan cross sectional. Besar sampel pada penelitian ini adalah 200 kasus rekam medis dengan menggunakan teknik simple random sampling. Analisis data menggunakan uji chi square. Hasil analisis kuantitatif rekam medis menunjukkan angka kelengkapan rekam medis sebesar 82,84%, dan tidak lengkap sebesar 17,16%. Pada analisis closed medical record review menunjukkan angka kelengkapan rekam medis sebesar 93,53%, dan tidak lengkap sebesar 6,47%. Hasil uji chi square menunjukkan bahwa tidak ada perbedaan yang signifikan proporsi kelengkapan antara hasil Analisis Closed Medical Record Review dengan hasil Analisis Kuantitatif rekam medis (nilai p.value=0,437 >0,05).Kata Kunci: Rekam Medis, Analisis Kuantitatif Rekam Medis, Analisis Closed Medical Record Review, Rumah Sakit Kanker “Dharmais”.